PWE-137 The epidemiology and outcome of biliary atresia in scotland 2002–2013. (22nd June 2015) - Henderson, P; Sutton, E; Tayler, R; Barclay, AR; Hansen, R
Abstract : Introduction: Biliary atresia (BA) is a rare and poorly understood liver disease of infancy that is fatal if not treated through early biliary drainage via the Kasai procedure. BA surgery was rationalised to three UK centres in 2002 following data supporting improved outcomes in institutions performing greater than five Kasai procedures per year. 1 We have previously shown that outcomes in Scottish children were worse than expected in the years following initial rationalisation. 2 We aimed to expand the post-rationalisation cohort of BA cases in Scotland to examine epidemiology and outcomes. Method: Outcomes of the previously published 2002–2009 incident cohort 2 was first expanded. New incident cases of BA, with a Scottish postcode at birth and born between 2010–2013, were obtained using data from specialist nurse/team knowledge in the three Scottish regional paediatric gastroenterology networks. New data collection focussed on demographics, details of Kasai and outcomes (particularly 2 year transplant-free survival [2YTFS]). Accurate regional and national population data was obtained from the General Register Office for Scotland and statistics performed in R with Poisson regression analysis for incidence trends. Results: 48 infants were initially identified, of whom 5 were excluded from outcome analysis (three with Kasai procedures performed in Edinburgh, one with less than 1 yr follow up post-Kasai and one child born outside Scotland). Three infants required immediate liver transplantation; 43 infants underwent Kasai. Median age at Kasai in the full cohort was 56 days (IQR 47–65) and showed significant improvement from 61 days in 2002–2009 to 51 days in 2010–2013 (p = 0.014). Of those with available data, 61% cleared their jaundice (bilirubin <20 umol/l) six months post-Kasai; 2YTFS was 45%. BA incidence in Scotland was 1 in 14, 745 live births and was relatively stable over time (1 in 15, 151 in 2002–2009 and 1 in 14, 084 in 2010–2013). However a cluster of cases was identified in Lanarkshire where the incidence was 1 in 7, 936 live births, significantly higher than the rest of Scotland (1 in 16, 949, p = 0.033). Conclusion: BA atresia incidence appears relatively stable in Scotland but with an unexplained cluster of cases in the Lanarkshire region; examination of this cluster may provide epidemiological insight into disease pathogenesis There was a significant reduction in time to Kasai portoenterostomy, with the 2YTFS improving since 2002–2009 cohort but is still lower than the pre-rationalisation figure of 65%. 2 Disclosure of interest: None Declared. References: McKiernan P, et al . Lancet. 2000;355(9197):25-29 Tayler R, et al . Arch Dis Child. 2013;98(5):381-383